VICTIM OF AN OFFENCE: LEGAL AND ECONOMIC ANALYSIS IN AN INTERJURISDICTIONAL CONTEXT - Andrii Borovyk; Oleksandr Golovach; Oleksandr Shyra (Baltic Journal of Economic Studies)
The paper addresses some criminal law and criminological issues related to the status and rights of crime victims. The study provides a comparative examination of the legal frameworks for crime victims in Ukraine, the United States and the European Union. It highlights significant differences in the definition of victim in Ukrainian criminal law and procedure, while discussing broader victim protection mechanisms in the American and European contexts. The subject of the study is an economic and legal analysis of the status of a crime victim in different jurisdictions. The chosen research methodology is based on the methods of systematic analysis, comparison and interdisciplinary (legal/economic) research. The purpose of this article is to propose, on the basis of a comprehensive analysis, some new approaches to understanding the concept of a crime victim in several world jurisdictions. The study draws conclusions of both theoretical and practical importance regarding the economic and legal status of crime victims at national and international levels. It is noted that, while the median economic losses from crimes are generally modest, crimes with significant financial impacts are rare but disproportionately covered in the media. The study places particular emphasis on the economic impact of crimes on victims and society as a whole. In addition to direct costs such as medical expenses, it also analyses indirect consequences including psychological trauma. The study furthermore includes an evaluation of restorative justice frameworks and victim compensation policies within the economic analyses of law framework. Moreover, the study underscores the pivotal role of international legal instruments, such as the EU's Directive 2012/29/EU and the International Criminal Court's provisions, in promoting universal enhancement of victims' rights. The authors advocate for further comparative research to harmonise national and international approaches to victim protection. It has been established that American federal law also recognises a special status of crime victims and contains a comprehensive legal protection framework to bring them justice. In comparison, the European model of protecting crime victims, as discussed in the paper, has been developed even further. It includes both legal mechanisms to protect victims within the EU and to monitor the progress of such protection at the international level. It has been demonstrated that the International Criminal Court (ICC) places significant emphasis on issues pertaining to victims by establishing a comprehensive procedural framework aimed at recognising and safeguarding the rights of victims subjected to various international crimes within the purview of the Court's jurisdiction.